Reconstruction of foot and ankle defects with a superthin innervated anterolateral thigh perforator flap. Issue 6 (1st November 2016) - Xie, Songlin; Deng, Xiangwu; Chen, Yanmin; Song, Dajiang; Li, Kanghua; Zhou, Xiao; Li, Zan
Abstract: Background: An anterolateral thigh (ALT) perforator flap can be thinned to an extent to which it is vascularised only by the subdermal plexus. This study presents an innervated flap thinning technique and its application for dorsal foot and ankle resurfacing. Methods: A superthin innervated ALT perforator flap was used to repair the dorsal foot and ankle of 12 patients. The perforators were classified according to their variations in the adipose layer, and the corresponding microdissection technique was then applied. The branch of the lateral femoral cutaneous nerve and its accompanying vessels were adopted to construct a sensory flap. Results: The flap thickness before defatting, which was measured immediately after flap elevation, ranged from 25–45 mm. The average flap thickness after defatting was 4.55 mm (range = 3–6 mm). A total of 11 flaps completely survived, and one flap presented superficial necrosis within a small area (2 cm ×2 cm) in the distal part of the flap. No further flap revision or defatting procedures were required for these patients during an average follow-up period of 16.5 months (range = 10–24 months). In the transferred flap, protective sensibility existed in all cases, and the static two-point discrimination was 13–16 mm. Conclusions: The superthin innervated ALT perforator flap may be considered as an ideal strategy for foot and ankle reconstruction.